Consumers’ Preference and Willingness to Pay for Imported Milk in the Seven Administrative Districts of Shanghai, China - Wei, Zhao; Wisedsind, Noppawan; Ruanggoon, Jirapong (Science, Technology, and Social Sciences Procedia, 2024)
The research objectives were as follows: 1) to assess consumer awareness regarding imported milk in the 7 administrative districts of Shanghai; 2) to investigate consumer preferences and willingness to pay for specific attributes of imported milk in the 7 administrative districts of Shanghai; and 3) to identify distinct consumer segments based on their preferences for imported milk attributes in the 7 administrative districts of Shanghai. The study utilized a choice experiment method to analyze consumer preferences for imported milk attributes in Shanghai. Five attributes were considered: fat content, flavor, nutritional enhancement, country of origin, and price. A questionnaire was designed, and data were collected from 310 respondents in Shanghai’s 7 districts. Two models, Random Parameter Logit (RPL) and Latent Class Modeling (LCM), were employed to estimate utility values for milk attributes. Statistics software was used for data analysis to identify differences in consumer perceptions. The research findings revealed that: 1) Consumer awareness of imported milk in Shanghai’s administrative districts was marked by distinct demographic profiles and consumption patterns. Most respondents were female, aged 25 - 34, with significant education levels and comfortable incomes. While milk consumption was prevalent, there was a preference for domestically produced milk, with limited uptake of imported dairy products and fortified foods. Different consumer segments exhibited varying levels of awareness and importance regarding nutritional claims, with “Nutrient-fortified” consumers showing the highest awareness; 2) Consumer preferences for imported milk in Shanghai revealed a preference for lower-priced, lower-fat, and original-flavored options, along with a strong preference for fortified milk enriched with vitamins and minerals. Country of origin influenced preferences, with German and New Zealand milk preferred over French milk. Consumers in Shanghai were willing to pay more for specific attributes of imported milk, such as lower-fat options and original flavors, while prioritizing nutrition and quality; and 3) Distinct consumer segments were identified in Shanghai based on preferences for imported milk attributes. The “Nutritional Fortification Preference” type prioritized health benefits and was willing to pay premiums for fortified varieties. The “No Difference” type showed minimal preference for specific attributes, emphasizing overall health claims. The “Taste Preference” type favored original-flavored milk, prioritizing taste and flavor. Lastly, the “Price-Sensitive” type prioritized affordability and exhibited lower willingness to pay premiums.